The stoma as a factor in determining the quality of life in patients with colorectal cancer - Stępień, Renata; Wiraszka, Grażyna; Wrońska, Irena; Nowak-Starz, Grażyna; Nemcova, Jana; Zdziebło, Kazimiera; Ratowska, Lidia (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Colorectal cancer (CRC), the most common malignant tumor of the gastrointestinal tract, is a serious and growing health problem not only in Poland but also in the world. Material and methods. The research was realized in 2011 in Świętokrzyski Cancer Centre in Kielce and the Public Health Care in Bochnia, including testing a total of 90 patients. The research tool was a questionnaire QOL-CR29. Results and conclusions. With the passage of time from diagnosis of the disease most of the symptoms is on the increase. Deteriorating the overall quality of life (p = 0.0065), there is reduced physical functioning (p = 0.0029). Elderly patients perform worse in cognitive functioning (p = 0.0027). Women worse social functioning than men (p = 0.0632). People with a stoma have a significantly lower level of capacity in the physical dimension. A major factor affecting the functional capabilities of patients is pain. The functional capabilities of patients with colorectal cancer were significantly dependent on the selected socio-demographic variables such as age, sex, education, marital status, fertility and the fact of having intestinal stoma and the level of pain. Nursing Topics 2014; 22 (2): 190–195